Ocean acidification and ammonium enrichment interact to stimulate a short-term spike in growth rate of a bloom forming macroalga - Reidenbach, Leah B.; Dudgeon, Steve R.; Kübler, Janet E. (Frontiers in Marine Science, 2022)
Introduction The coastal macroalgal genus, Ulva, is found worldwide and is considered a nuisance algal genus due to its propensity for forming vast blooms. The response of Ulva to ocean acidification (OA) is of concern, particularly with nutrient enrichment, as these combined drivers may enhance algal blooms because of increased availability of dissolved inorganic resources. Methods We determined how a suite of physiological parameters were affected by OA and ammonium (NH4+) enrichment in 22-day laboratory experiments to gain a mechanistic understanding of growth, nutrient assimilation, and photosynthetic processes. We predicted how physiological parameters change across a range of pCO2 and NH4+ scenarios to ascertain bloom potential under future climate change regimes. Results During the first five days of growth, there was a positive synergy between pCO2 and NH4+ enrichment, which could accelerate initiation of an Ulva bloom. After day 5, growth rates declined overall and there was no effect of pCO2, NH4+, nor their interaction. pCO2 and NH4+ acted synergistically to increase NO3- uptake rates, which may have contributed to increased growth in the first five days. Under the saturating photosynthetically active radiation (PAR) used in this experiment (500 μmol photon m-2 s-1), maximum photosynthetic rates were negatively affected by increased pCO2, which could be due to increased sensitivity to light when high CO2 reduces energy requirements for inorganic carbon acquisition. Activity of CCMs decreased under high pCO2 and high NH4+ conditions indicating that nutrients play a role in alleviating photodamage and regulating CCMs under high-light intensities. Discussion This study demonstrates that OA could play a role in initiating or enhancing Ulva blooms in a eutrophic environment and highlights the need for understanding the potential interactions among light, OA, and nutrient enrichment in regulating photosynthetic processes.